2003
DOI: 10.1073/pnas.1330865100
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the hexose transporter of Plasmodium falciparum as a novel drug target

Abstract: Chemotherapy of malaria parasites is limited by established drug resistance and lack of novel targets. Intraerythrocytic stages of Plasmodium falciparum are wholly dependent on host glucose for energy. Glucose uptake is mediated by a parasite-encoded facilitative hexose transporter (PfHT). We report that O-3 hexose derivatives inhibit uptake of glucose and fructose by PfHT when expressed in Xenopus oocytes. Selectivity of these derivatives for PfHT is confirmed by lack of inhibition of hexose transport by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
159
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(166 citation statements)
references
References 16 publications
(17 reference statements)
7
159
0
Order By: Relevance
“…A study using O-3 hexose derivatives demonstrated a potent and selective inhibition of PfHT. Moreover, the glucosederived inhibitors show an inhibition of asexual blood stage P. falciparum growth in vitro and of different P. berghei life cycle stages in vivo, thereby validating PfHT as a valuable antimalarial drug target (46). This assumption was further supported by a study showing that PfHT is essential for both P. falciparum and P. berghei (47).…”
Section: P Falciparum Glucose Transportersmentioning
confidence: 73%
“…A study using O-3 hexose derivatives demonstrated a potent and selective inhibition of PfHT. Moreover, the glucosederived inhibitors show an inhibition of asexual blood stage P. falciparum growth in vitro and of different P. berghei life cycle stages in vivo, thereby validating PfHT as a valuable antimalarial drug target (46). This assumption was further supported by a study showing that PfHT is essential for both P. falciparum and P. berghei (47).…”
Section: P Falciparum Glucose Transportersmentioning
confidence: 73%
“…The increase in levels of N-carbamoyl-L-aspartate and dihydroorotate in atovaquone-treated cultures reflects the indirect inhibition of dihydroorotate dehydrogenase activity following primary inhibition of ubiquinol oxidation by the cytochrome bc 1 complex (22). Interestingly, primaquine and the metabolic inhibitors, buthionine sulfoximine, 2-deoxyglucose, compound 3361 (45), and sodium fluoroacetate did not elicit reproducible metabolic fingerprints under these conditions ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 94%
“…3A). Similarly, other genes needed for the acquisition of nutrients in the malarial parasite such as PfHT and PfNT1 (malaria hexose transporter and nucleoside transporter) have been shown to be up-regulated during the trophozoite/ schizont stages (7,8).…”
Section: Discussionmentioning
confidence: 99%